Перспективи використання інноваційних технологій у вдосконаленні засобів індивідуального захисту - Юзифович, Р. Ю. (ХНУРЕ, 2024)
Personal protective equipment is a key element in ensuring the protection of employees from harmful production factors. This paper discusses methods of improving the effectiveness of protective equipment by introducing innovative technologies into their development. Particular attention is paid to such innovations as exoskeletons, augmented reality, wearable technologies and nanomaterials. The prospects of integrating these technologies into PPE are analyzed and a conclusion is made as to whether they can become a standard in labor protection.
Keywords: індивідуальний захист